Lifetime assessment of solid-state hybrid supercapacitors based on cotton fabric electrodes - Vieito, António Jose Paleo (2019)
Electrodes based on activated carbon and manganese oxide coated on a cotton woven fabric were developed and investigated. The electrodes were then assembled with two polymer electrolyte membranes, Nafion®115 and Aquivion®E87-05S, and two different supercapacitors were produced with specific capacitances and energy densities of 130 and 132 F g−1, and 11.5 and 11.7 Wh kg−1, respectively. Furthermore, a new durability methodology, which combines galvanostatic charge/discharge cycles together with potentiostatic floating conditions, was used to get insight into their electrochemical performance under stringent conditions. The supercapacitor assembled with Nafion®115 electrolyte worked successfully for 10 k cycles and 140 h under a constant voltage of 1.6 V (floating condition), whereas the supercapacitor assembled with Aquivion®E87-05S electrolyte worked successfully for more than 15 k cycles and 210 h, without any appreciable degradation of their electrochemical properties. In summary, hybrid solid-state supercapacitors based on electrodes produced by simple methodologies and low-cost materials, and with long durability performance under very harsh conditions were developed and analysed for their potential utilization as flexible energy storage devices.